"Hematological and biochemical indices of breeder cocks fed Cottonseed cake " (2004)
" Hematological and' biochemical profiles of 30 breeder cocks were investigated in a completely randomized design using replacement level of 0, 25, 501 75 and 100% of Cottonseed cake (CSC) for Soybean cake (SSC). Blood samples were collected at the 4th and 8th weeks of the feeding trial for analyses. The result showed no significant differences (p.>0.05) in Packed Cell Volume (PCV), Red Blood Cells (RBC), White Blood Cells (WBC) and Haemoglobin (Hb) of the bird at the fourth week of the experiment. But at the eight week of the trial, the Hb (13 .89-69kg/dl) was significantly higher (p<0.05) in 75% CSC fed birds than the lower and 100% inclusion. Lymphocytes (Lym) of75% CSC fed birds were significantly higher at the fourth week of trial than those on lower or 100% inclusions . Similarly, at the 41hweek, the Neutrophils (47.89-52.73%) of 50% CSC fed birds were significantly higher than those on lower or higher' inclusion levels. Effects of diet were not apparent in the total protein, albumin and globulin fractions of the bird at the 41h and 81hweek of the experiment. The investigaton showed that replacing 75% soybean cake with CSC was not injurious to the health of breeder cocks. "